Effect of Bradyrhizobium and Azotobacter on growth and yield of mungbean varieties - Ara, Nazmun; Rokonuzzaman, M; Hasan, MN (Journal of the Bangladesh Agricultural University, 2010)
A field experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University (BAU), Mymensingh during the period from January to April 2004 to study the effects of Bradyrhizobium and Azotobacter inoculation on growth and yield of mungbean varieties. There were ten treatment combinations taking two varieties of mungbean viz. BARI mung-3 and BARI mung-4, and five bacterial and chemical fertilizers viz.control, Bradyrhizobium, Azotobacter, Bradyrhizobium plus Azotobacter and 20 kg N ha-1. The experiment was laid out in a split plot design with three replications assigning varities in main plots and bacterial and chemical fertilizers in subplots. The unit plot size was 4 m x 3 m. After 35 days of sowing, 10 plants were randomly uprooted from each plot to study nodulation. At maturity yield and yield contributing characters were recorded. Variety BARI mung-3 recorded significantly higher nodule number and weight, and shoot weight compared to BARI mung-4. On the other hand, BARI mung-4 produced significantly higher seed and stover yields than BARI mung-3 did. Application of Bradyrhizobium or Azotobacter or their combination significantly increased nodulation, and root and shoot weights at 35 days after sowing. Similarly, the number of seeds pod-1 and seed yield were significantly influenced by the bacterial biofertilizer. These results indicate that use of both Bradyrhizobium and Azotobacter inoculants appears to be an effective method for successful mungbean production at BAU farm. Keywords: Growth; Yield; Mungbean; Bradyrhizobium; Azotobacter DOI: 10.3329/jbau.v7i1.4790 J. Bangladesh Agril. Univ. 7(1): 7-13, 2009